CORELAŢIA DINTRE IDEOLOGIE ŞI PROCESUL POLITIC ÎN SOCIETATEA DE TRANZIŢIE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2007)
In this study the corelation between the political ideology and the political process in the context of transition society, as Republic of Moldova is analysed. Also, it focused on the pecularities of political process of transition in Republic of Moldova, its problems and errors: the impact of ideology on the politics.